Pricing Methods for a Leasing Service (Путеводитель предпринимателя, 2020)
The article considers the diversity of pricing methods for leasing services in Russian Federation on a stage of leasing projects structuring as well as defines their place in development of suggestions for recipients of leasing aimed at creation of higher value for the end consumer